Personal norms - and not only social norms - shape economic behavior - Zvonimir Baésic; Eugenio Verrina (Max Planck Institute for Research on Collective Goods, 2020)
While social norms have received great attention within economics, little is known about the role of personal norms. We propose a simple utility framework - which assumes that people care about monetary payoff, social norms, and personal norms - and design a novel two-part experiment to investigate the predictive value of personal norms across four economic games. We show that personal norms - together with social norms and monetary payoff - are highly predictive of individuals' behavior. Moreover, they are: i) inherently distinct from social norms across a series of economic contexts, ii) robust to an exogenous increase in social image concerns, which increases the predictive value of social norms, but does not weaken that of personal norms, and iii) complementary to social norms in predicting behavior, as a model with both personal and social norms outperforms a model with only one of the two norms. Taken together, our results support personal norms as a key driver of economic behavior, relevant in a wide array of economic settings.
Keywords: C91; D01; D63; D64; D91; 330; Personal norms; social norms; social image; elicitation method; normative conflict